Prevention and Legal Protection for Victims of Human Trafficking and Drug Abuse Offenses - Pradini, Yustia Okta; Anjani, Maudy; Hosnah, Asmak Ul (PT FORMOSA CENDEKIA GLOBAL, 2024)
Human trafficking and drug abuse are two complex problems that have a serious impact on people’s lives globally. Besides threatening human rights, human trafficking and drug abuse also damaged individual welfare, disrupt the social order, and also harm the aspect of economies to all countries. Generally, human trafficking involves forced labor, organ trafficking, and also sexual exploitation, which are very damaging and harmingthe victims. On the other hand, drug abuse has became rampant like a pandemic that has spread all around the world and affected the society. Drugs can be very harming, apart from causing a physical harm, it also can caused a mental illnes to it’s victim. In this research, authors will examine the relation between human trafficking and drug abuse, identify how to prevent and also to found the legal protection for the victims.